A Tetranuclear Silver-Thiourea Cluster - Fernandes, Jose A.
During the synthesis of the bioactive complex [Ag(phen)(mu-tu)](2)(NO3)(2) (1), some crystals of a new compound were isolated. This crystalline compound, [Ag-4(mu-tu)(5)(tu)(6)](NO3)(4)center dot 7Phen (2) (tu = thiourea, Phen = 1,10-phenanthroline), is a novelty for at least two reasons: (i) it is the first tetranuclear silver and thiourea cluster; (ii) it is the first crystal structure with seven neutral, and uncoordinated, phen molecules. Phen molecules pack forming an infinite column, and the tu ligands form an intricate network of hydrogen bonds with the Phen and nitrate entities. The new compound [Ag-4(mu-tu)(5)(tu)(6)](NO3)(4)center dot 7Phen (tu = thiourea, Phen = 1,10-phenanthroline) is a novelty at least by two ways: (i) it is the first tetranuclear cluster of silver and thiourea; (ii) it is the first crystal structure with seven neutral, and uncoordinated, phen molecules. [GRAPHICS] .